2018
DOI: 10.1080/01635581.2018.1460677
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Ketogenic Diet in Adults with Glioblastoma: An Evaluation of Feasibility and Deliverability within the National Health Service

Abstract: There is an increasing interest in the use of the ketogenic diet (KD) as an adjuvant therapy for glioma patients. We assessed the tolerability and feasibility of a modified ketogenic diet (MKD) in patients with glioma, along with willingness of patients to participate in future randomized controlled trials. The study was undertaken in two parts; a patient questionnaire and evaluation of the diet. One hundred and seventy-two questionnaires were completed; 69% (n = 119) of the population reported MKD should be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 22 publications
0
56
0
Order By: Relevance
“…Out of the 12 patients randomized, 10 commenced KD and only four met the primary endpoint of three-month dietary intervention (1 KD, 3 MKD). Cancer trials in general report median retention rates of 89% (IQR 79-97% with valid primary outcome data at follow up) [33] and previous KD studies for patients with GBM report retention rates of 50 to 100%, with retention determined at eight weeks [19], three months [18,32] and the point of tumor progression [17]. However, patients in these previous KD studies self-selected to try the diet, mainly at recurrence or post-treatment, creating an optimistic bias in retention, when compared to the general unselected GBM population approached for KEATING.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Out of the 12 patients randomized, 10 commenced KD and only four met the primary endpoint of three-month dietary intervention (1 KD, 3 MKD). Cancer trials in general report median retention rates of 89% (IQR 79-97% with valid primary outcome data at follow up) [33] and previous KD studies for patients with GBM report retention rates of 50 to 100%, with retention determined at eight weeks [19], three months [18,32] and the point of tumor progression [17]. However, patients in these previous KD studies self-selected to try the diet, mainly at recurrence or post-treatment, creating an optimistic bias in retention, when compared to the general unselected GBM population approached for KEATING.…”
Section: Discussionmentioning
confidence: 97%
“…Previous feasibility work estimated recruitment targets of one patient per month [32], in keeping with National Institute for Health Research (NIHR) funded trials [33]. Twelve patients were to be recruited over 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recently published survey among high grade glioma patients revealed that almost three quarters (73%) of patients would be willing to try a KD for three months and 66% would participate in a clinical trial investigating the effectiveness of the KD. 5 …”
Section: Introductionmentioning
confidence: 99%
“…A list of relevant KD studies published in peer-reviewed journals is given in Table 1, and Fig. 3 shows their chronological appearance relating to Brünings’ publications 7 , 10, 11, 12, 13, 14 , 32 , 34 , 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65. It took almost half a century after Brünings’ first publication until what is generally considered the first clinical study treating cancer patients with a KD was published (Fearon et al.…”
Section: Discussionmentioning
confidence: 99%